Föreställningar om kunskap och lärande i lärares planeringssamtal i matematik och historia - Randahl, Ann-Christin; Liljekvist, Yvonne; Jakobsson, Martin; Nordgren, Kenneth (Utbildning & Lärande, 2023)
This article reports a study of teachers’ lesson planning in a collegial setting. The school employed scheduled time every week for team planning in different school subjects. In this article, 44 planning sessions in Mathematics and History are analysed in two steps. First, the sessions were coded in Nvivo with a framework building on Tyler’s (1950) description of planning as a four-step activity. In a second step, beliefs about knowledge and knowers were analysed using the concepts of hierarchical and horizontal knowledge and knower structures (Maton, 2014). The results reveal that time spent on discussing specific activities in regard to planning differed considerably. For example, the planning team in History spent 36% on specifying objectives and knowledge whereas the planning team in Mathematics spent 5,5% on that theme. Further, different beliefs about knowledge and knowers in the two subjects appeared, where a hierarchical knowledge structure and a horizontal knower structure was identified in Mathematics and a horizontal knowledge structure and a hierarchical knower structure was identified in History. These divergences in coding orientation and focus in planning between school subjects indicate that lesson planning is a subject specific practice that needs to be organised for in teachers’ daily work.